Entrepreneurship is not a binding constraint on growth and development in the poorest countries - Wim Naudé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
It is often claimed that entrepreneurship is indispensable for economic growth and development. These claims are mostly generated by scholars working in the field of entrepreneurship and management studies. In contrast, development economics scholars seem to be less concerned about entrepreneurship in the development process Who is right? I show that the arguments and evidence marshalled so far fails to convincingly show that entrepreneurship is a binding constraint on development in the poorest countries. In development economics institutional weakness, not entrepreneurship, is considered by many to be a more binding constraint on development, especially over the long run. However, recent advances at the interface of entrepreneurship and development economics suggest that unpacking the black box nature of institutions may benefit from incorporating an entrepreneur. Thus, even if entrepreneurship is not a binding constraint on economic development, it may still be worthwhile to study entrepreneurship in development as it may improve our understanding of the real binding constraints.
Keywords: L26; O10; 330; entrepreneurship; development; development economics; institutions; Entwicklung; Entrepreneurship-Ansatz; Entwicklungstheorie; Vierte Welt